Manajemen Personalia Lembaga Pendidikan: MA Darul Ihsan Samarinda dan SMA YPM Diponogoro Tenggarong Seberang - Fuad, Misbahul (SYAMIL: Journal of Islamic Education, 2019)
In its development, madrasas experienced ups and downs in their development. The most basic problem is the management aspect. The following cases of management are interesting to note. There are schools or madrasas that initially experience setbacks, then can progress rapidly. On the other hand, there are schools or madrassas that initially developed, but then almost went out of business. One of the reasons is due to the management that is not mature enough, therefore personnel management in the world of education is very important especially in educational institutions especially Islamic-based educational institutions. This study aims to determine the application of personnel management in Islamic education institutions and supporting and inhibiting factors in its application. This research is a type of field research with a multi-case study research approach. Data collection methods used Participatory Observation and In-depth interviews. The steps of data analysis in this study use the analysis of the Miles and Huberman models. Based on the results of research in the field it was found that: 1) The implementation of personnel management in MA Darul Ihsan Samarinda and YPM Diponegoro Tenggarong Seberang High School which consisted of educators and education staff. There are several components of personnel management, including seven components that have different divisions and elements, namely planning, recruitment, coaching, dismissal, but there are three important components that have not been comprehensively applied, namely compensation, appointment and evaluation. 2) Supporting factors for the implementation of personnel management in MA Darul Ihsan Samarinda and YPM Diponegoro Tenggarong Seberang High School are the motivation given by the madrasa headmaster and headmaster to their personnel so that they always try to be better and give encouragement or enthusiasm in carrying out their tasks. Both vision, mission, goals because each institution must have a vision, mission and goals as well as MA Darul Ihsan Samarinda and YPM Diponegoro Tenggarong High School have a vision, mission and clear objectives, while the inhibiting factor in the implementation of personnel administration is a means of implementing administration in MA Darul Ihsan Samarinda and YPM Diponegoro Tenggarong Seberang High School due to the unavailability of sufficient funds and human resources in their fields.